The Symbol of Pak Ngambung Figure in Sukuraga Puppet - Anugrah, Riana Putri (PT. Alahyan Publisher Sukabumi, 2023)
This study is aims to explain the symbol and the meaning of Pak Ngambung Figure in Sukuraga Puppet. Sukuraga puppets is an original art from Sukabumi. Sukuraga puppets is one of the arts that belongs to the category of contemporary puppets, because it brings out stories and characters that are unique to this puppets itself. The characters are named and shaped like body part, such as Pa Anon (panon) meaning eyes, pa gambung (irung) meaning nose, mullut or mouth, Ceu Pil (Ceupil) meaning ears, lengeun (hands), kudu leumpang (kaki) and so on. One of the characters from the sukuraga puppets that the author considers to be quite interesting is the character pa bung (irung) or nose. The nose in our body has a very important role, because the nose functions to breathe. in this study using descriptive qualitative method. the writer collects data qualitatively and describes it in a descriptive way.